Simplify: 12(2 + 3x - 6)
= (12)(2 + 3x + - 6) = (12)(2) + (12)(3x) + (12)( - 6)
= 24 + 36x - 72
Answer = 36x - 48
2: Factor:
36x - 48
= 12(3x -4)
Answer
= 12(3x -4)
3: <span>12(2+3x−6)
= 12(3x + 2 - 6)
= 12(3x - 4)
Your Answer would be (A).
3x - 4</span>
Answer:
$163
Step-by-step explanation:
Bob worked 26 hours and earn $7 per hour. Multiply 26 with 7:
26 x 7 = 182
Bob made a total of $182 last month.
Bob then spent $19. Subtract 19 from the total earned:
182 - 19 = 163
Bob has $163 left.
~
Answer:
NPL
Step-by-step explanation:
The angles across from each other on a parallelogram are congruent
$1468.05...............................
Answer:
A+*in a house*127^0/0
underfined
Step-by-step explanation: